REKONSTRUKSI PENDIDIKAN ISLAM DI ERA SOCIETY 5.0 - Muhammad Nasikin; Khojir Khojir (Cross-border, 2021)
The flow of reconstructionism is one of the schools in educational philosophy that seeks to overhaul the old order and build a modern-style structure of cultural life and seeks to find agreement between human beings or to be able to regulate the order of human life in an order and the entire environment. The development of information technology is currently reaching all levels of society, including in education, especially Islamic education. In the era of the industrial revolution 4.0, three literacies are needed, namely data literacy, human literacy, and technological literacy. Learning in the 4.0 revolution era can apply hybrid/blended learning and case-based learning. Even education in the era of society 5.0, allows students or students in learning activities side by side with robots that have been designed to replace the role of educators. This paper examines the reconstruction of the Islamic religious education in welcoming the era of society 5.0. Thus, education activists and stakeholders get an idea of ​​the urgency of the presence of technology in the era of society 5.0 in the world of Islamic education.